A titanium implant surface coating promoting bone integration and preparation method thereof

By constructing a hydrogel coating on the surface of titanium implants, the timing M1/M2 polarization of macrophages was achieved, and the problems of acute inflammation and poor biological factor activity during the titanium implant surface were solved, and the effects of antibacterial, bone tissue healing and bone integration were achieved.

CN118436847BActive Publication Date: 2025-04-22CHINA THREE GORGES UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410470001.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-18
Publication Date
2025-04-22
Estimated Expiration
2044-04-18

AI Technical Summary

Technical Problem

The titanium implant surface induces macrophage timing polarization problems with initial acute inflammation, poor biological factor/drug activity and bioindifference on the implant surface.

Method used

By constructing a hydrogel coating on the surface of titanium implants, macrophage M1 polarization was induced in the early stage and macrophage M2 polarization was induced in the later stage, achieving the synergistic effects of antibacterial, bone tissue healing, inhibition of fibrosis and promoting bone integration.

Benefits of technology

It effectively reduces initial acute inflammation, improves biofactor activity, enhances biocompatibility on the surface of the implant, and promotes bone-titanium integration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118436847B_ABST
    Figure CN118436847B_ABST
Patent Text Reader

Abstract

The present invention discloses a titanium implant surface coating that promotes bone integration and a preparation method thereof, wherein a hydrogel coating is constructed on the titanium surface by initiating free radical polymerization through ultraviolet-triggered surface catalysis. The present invention constructs a hydrogel coating on the titanium implant surface, and loads two drugs that can induce macrophages to polarize to M1 and M2 types respectively by means of swelling absorption and reversible chemical bonds, thereby achieving precise induction of the sequential M1 / M2 polarization of macrophages accumulated at the bone-titanium interface, thereby achieving the synergistic effects of antibacterial, bone tissue healing, inhibition of fibrosis and promotion of bone integration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a titanium implant surface coating for promoting bone integration and a preparation method thereof, and belongs to the technical field of medical materials. Background Art

[0002] In the field of plastic surgery, titanium implants are widely used in the structural and functional reconstruction of bones and teeth. However, poor bone integration greatly limits the implantation success rate and service life of titanium implants. Good bone-titanium integration usually originates from the strong interfacial interaction between the titanium surface and the surrounding bone tissue at the molecular and cellular levels, and its bonding strength is highly dependent on the degree of vascularization, new bone formation and calcium mineralization / deposition of the titanium surface. Traditional strategies to enhance bone-titanium integration focus on constructing an osteoconductive or osteoinductive titanium surface microenvironment, and its target cells mainly include bone mesenchymal stem cells (BMSCs), osteoblasts and osteoclasts. In recent years, with the development of osteoimmunology, immune regulation-mediated new bone formation has attracted great attention and has shown great potential in promoting bone-titanium integration. In the process of bone immune regulation, macrophages play the role of a regulatory center.

[0003] As a highly plastic cell, macrophages play a key immunomodulatory role in resisting infection and inducing bone regeneration. After titanium is implanted in the body, neutrophils induce acute inflammation within a few hours, followed by a large number of monocytes rapidly migrating from the periphery to the defect site. Afterwards, monocytes rapidly differentiate into M0 macrophages, which aggregate at the bone-titanium interface and become the main cell type. Under external stimulation, M0 macrophages can polarize to the classically activated M1 phenotype or the alternatively activated M2 phenotype, and M1 macrophages can also polarize to the M2 phenotype. M1 macrophage exosomes (such as CCL2, CXCL8, SDF-1, TNF-α, IL-6, and IL-8) can aggravate the inflammatory response, limit fibrosis, recruit other immune cells (such as B cells and T cells) to clear damaged bone tissue, and recruit vascular progenitor cells (VPCs) and bone marrow mesenchymal stem cells to initiate bone regeneration. M2 macrophage exosomes (such as IL-10, IL-4, TGF-β, ARG-1, BMP-2, VEGF) can relieve inflammatory responses, restore bone homeostasis, and induce endothelial cell differentiation and bone marrow mesenchymal stem cell osteogenic differentiation. In recent years, many studies have shown that short-term induction of in situ M1 macrophage polarization or induction of in situ M2 macrophage polarization can promote bone-titanium integration. Considering that in the normal bone healing process, M0 macrophages are temporarily polarized to M1 phenotype in the initial stage (the first 3 days) and then converted to M2 phenotype, more and more researchers believe that compared with the above two immune regulation strategies, sequential induction of in situ M1 / M2 macrophage polarization can better promote bone-titanium integration. However, a long-term M1 macrophage-dominated immune environment can lead to excessive or chronic inflammation, damage tissues, accelerate fiber formation, and ultimately lead to poor tissue healing. In the ideal tissue repair process, a timely and effective conversion of macrophage phenotype from M1 to M2 is necessary. Summary of the invention

[0004] The purpose of the present invention is to solve the problems of severe initial acute inflammation, poor activity of biological factors / drugs and biological inertness of the implant surface when inducing macrophage sequential polarization on the titanium surface. The present invention achieves the synergistic effects of antibacterial, bone tissue healing, inhibition of fibrosis and promotion of bone integration by constructing a hydrogel coating with strong bonding strength on the titanium implant surface, excellent mechanical stability and fatigue resistance under repeated stress, and sequentially regulating the phenotypic transformation of macrophages, inducing macrophage M1 polarization in the early stage and inducing macrophage M2 polarization in the late stage.

[0005] To achieve the above object, the technical solution adopted by the present invention is: a titanium implant surface coating promoting bone integration and a preparation method thereof, comprising the following steps:

[0006] (1) The original titanium sheet was polished with sandpaper, washed with different solvents, and dried;

[0007] (2) Soaking the titanium sheet treated in step (1) in concentrated sulfuric acid and piranha washing solution in turn, leaving it at room temperature for a period of time, then taking it out, washing it with ultrapure water and ethanol, drying it, and setting it aside;

[0008] (3) Soaking the titanium sheet treated in step (2) in a dopamine hydrochloride solution overnight in a dark and aerobic environment, rinsing three times with deionized water, and drying;

[0009] (4) immersing the titanium sheet treated in step (3) in a mixed solution of ferric chloride hexahydrate and citric acid, taking it out and exposing it to ultraviolet light, then immersing the treated material in a monomer solution containing hydroxyethyl methacrylate, taking it out and leaving it at room temperature overnight;

[0010] (5) The titanium sheet treated in step (4) is sequentially immersed in an ethanol solution of luteolin and an aqueous solution of sophoridine for balanced swelling, thereby preparing a titanium implant surface coating that promotes bone integration.

[0011] Preferably, the solvent in step (1) comprises acetone, ethanol, or deionized water for ultrasonic washing.

[0012] The specific operation steps in step (1) are as follows: a circular titanium sheet is polished with #800 and #1600 sandpaper, rinsed with deionized water three times, ultrasonically washed with acetone, ethanol, and deionized water three times, each time for 5 minutes, and dried in an oven at 60°C. The titanium sheet has a diameter of 10-14.8 mm and a thickness of 0.5-1 mm.

[0013] Preferably, in step (2), the concentration of concentrated sulfuric acid is 98% or above; the volume ratio of piranha wash solution is 3-5:1 of concentrated sulfuric acid of 98% or above and 30-40% hydrogen peroxide. Hydroxyl groups are introduced into the surface of the titanium sheet in the above manner.

[0014] Preferably, in step (3), the dopamine hydrochloride in step (3) is dissolved in 5-10 mM Tris-HCl buffer, pH 8.0-8.5, with a concentration of 2-5 mg / mL.

[0015] In some preferred embodiments, the dopamine hydrochloride is dissolved in 10 mM Tris-HCl buffer at pH 8.5 at a concentration of 2 mg / mL, so that a uniform polydopamine coating is formed on the surface of the titanium sheet.

[0016] Preferably, in the mixed solution of step (4), the mass concentration of ferric chloride hexahydrate is 0.03-0.04 g / mL; the mass concentration of citric acid is 0.03-0.04 g / mL; the pH of the mixed solution before immersion is adjusted to 3-5. The ultraviolet light irradiation conditions are 300-370 nm and 10-20 W for 3-10 minutes to make Fe 3+ Reduction to Fe 2+ .

[0017] The monomer solution of hydroxyethyl methacrylate is hydroxyethyl methacrylate, N , A mixed solution formed by N-methylenebisacrylamide, ammonium persulfate and 3-acrylamidophenylboronic acid; the concentrations of each are 1-1.5 g / mL, 1-3 mg / mL, 2-5 mg / mL, and 0.5-0.7 mg / mL.

[0018] The titanium sheet after ultraviolet light reduction is then immersed in a monomer solution containing hydroxyethyl methacrylate for 3-5 minutes, taken out, and then left to cure at room temperature for 10-15 minutes, after which the monomers that have not participated in the reaction are washed off, and then left to stand at room temperature overnight to form a uniform hydrogel coating on the surface of the titanium sheet.

[0019] Preferably, in step (5), the concentration of the alcohol solution of luteolin is 0.1-1.0 mg / mL, preferably 0.5 mg / mL; the alcohol solution comprises a C1-C4 alcohol solvent;

[0020] The concentration of sophoridine is 1.0-5.0 mg / mL, preferably 1.5 mg / mL.

[0021] Luteolin was bound via reversible phenylboronate interaction, while sophoridine was physically loaded inside the hydrogel.

[0022] The beneficial effects of the present invention are as follows: the titanium implant surface coating and preparation method thereof provided by the present invention initiates free radical polymerization through ultraviolet-triggered surface catalysis, and constructs a hydrogel coating on the titanium implant surface starting from the viscous initiation layer of polydopamine. Then, the obtained implant loaded with the coating is subjected to equilibrium expansion in an ethanol solution of luteolin and an aqueous solution of sophoridine in turn, and the sequential release of sophoridine and luteolin is mediated by the gradually decreasing hydroxide concentration inside the hydrogel, so as to achieve precise induction of the sequential M1 / M2 polarization of macrophage accumulation at the bone-titanium interface, thereby achieving the synergistic effects of antibacterial, bone tissue healing, inhibition of fibrosis and promotion of bone integration, and not only developing a new titanium implant coating that promotes bone integration through immune regulation, but also providing certain inspiration for the future research and development of titanium implants. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic diagram of the preparation of the hydrogel coating on the titanium surface in Example 1, wherein A is the structural formula of sophoridine and luteolin and the schematic diagram of the ionization of sophoridine in water, B is a schematic diagram of the preparation of the composite hydrogel coating on the titanium surface, C is a schematic diagram of the composite hydrogel coating for the timed delivery of sophoridine and luteolin; D is a schematic diagram of the composite hydrogel coating for the timed induction of M1 / M2 macrophage polarization.

[0024] Figure 2 The following are actual pictures of the titanium surfaces of each group during the preparation process of Example 1, where A is a titanium sheet and B is a titanium nail.

[0025] Figure 3 These are the surface morphology results of each group of titanium sheets during the preparation process of Example 1.

[0026] Figure 4 These are the atomic force microscope results of each group of titanium sheets during the preparation process of Example 1 of the present invention.

[0027] Figure 5 The following are Fourier transform infrared spectra of each group of titanium sheets during the preparation process of Example 1.

[0028] Figure 6 The figure is a graph showing the mechanical properties test results of the titanium implant surface coating for promoting bone integration prepared in Example 1; wherein A is a schematic diagram of the experimental device for testing the lap shear strength of the titanium surface hydrogel coating; B is the bonding strength of different titanium surface hydrogel coatings prepared in Example 1 and Example 4; C is the force-displacement curve of the titanium implant surface coating for promoting bone integration prepared in Example 1 after five consecutive loading-unloading tests; and D is the bonding strength retention rate in five consecutive loading and unloading tests.

[0029] Figure 7 The results of the hydrogel coating on the titanium implant surface prepared in Examples 1, 2, and 3 for sustained release of sophoridine and luteolin in a simulated physiological fluid environment (pH=7.4) are shown in Figure 1. A is a schematic diagram of sustained release of sophoridine in Example 3, B is a schematic diagram of sustained release of luteolin and sophoridine in Example 1, and C is a schematic diagram of sustained release of luteolin in Example 2.

[0030] Figure 8 The graphs show the effects of different groups of titanium sheets prepared in Examples 1, 2, and 3 on bone marrow mesenchymal stem cells (BMSCs) and mouse mononuclear macrophage leukemia cells (RAW264.7).

[0031] Fig. 9 qPCR analysis of the expression of inflammation-related genes in RAW264.7 cells after incubation for 2 and 4 days with different groups of titanium sheets prepared in Examples 1, 2, and 3, and ELISA analysis of the expression of inflammation-related genes in RAW264.7 cells after incubation for 2 and 4 days with different groups of titanium sheets prepared in Examples 1, 2, and 3.

[0032] Fig.10 Representative fluorescence images and corresponding quantitative statistical graphs of iNOS and CD206 after different groups of titanium sheets prepared in Examples 1, 2, and 3 were incubated with RAW264.7 cells for 2 and 4 days.

[0033] Fig.11 Representative staining images and quantitative analysis of alkaline phosphatase and alizarin red staining of different groups of titanium sheets prepared in Examples 1, 2, and 3.

[0034] Fig.12 Representative H&E and immunohistochemical staining images of different groups of titanium sheets prepared in Examples 1, 2, and 3 at day 7 after implantation.

[0035] Fig.13 Micro-CT 3D reconstruction images of new bone formation and trabecular thickness around implants were measured at a scale of 1 mm after 4 weeks of surgical implantation of different groups of titanium sheets prepared in Examples 1, 2, and 3. Quantitative analysis of bone volume / total volume (BV / TV), trabecular number (Tb.N), and trabecular spacing (Tb.Sp) was also performed. DETAILED DESCRIPTION

[0036] Example 1

[0037] This embodiment provides a method for preparing a titanium implant surface coating that promotes bone integration. Figure 1 The preparation method is carried out according to the principle and process of the following method, comprising the following steps:

[0038] (1) Take a circular titanium sheet with a diameter of 14.8 mm and a thickness of 1 mm, polish it with #800 and #1600 sandpaper respectively, rinse it with deionized water three times, ultrasonically wash it with acetone, ethanol, and deionized water three times, each time for 5 min, and place it in a 60°C oven to dry;

[0039] (2) The titanium sheet treated in step (1) was immersed in concentrated sulfuric acid and piranha wash solution (98% concentrated sulfuric acid: 30% hydrogen peroxide = 1:1, v / v) in turn, left to stand at room temperature for 1 hour, then taken out, washed with ultrapure water and ethanol three times each, dried, and set aside to introduce hydroxyl groups onto the surface of the titanium sheet, recorded as Ti-OH;

[0040] (3) placing the titanium sheet treated in step (2) in a dopamine hydrochloride solution, wherein the dopamine hydrochloride is dissolved in 10 mM Tris-HCl buffer at a pH of 8.5 to a concentration of 2 mg / mL, soaking overnight in a dark and aerobic conditions, rinsing three times with deionized water, and drying to form a uniform polydopamine coating on the surface of the titanium sheet, which is recorded as Ti-PDA;

[0041] (4) Dissolve 1.182 g of citric acid and 1.018 g of ferric chloride hexahydrate in 30 mL of deionized water, and drop 1 mol / L NaOH solution until the pH reaches 4.0. Then, soak the titanium sheet treated in step (3) in the above solution for 3 hours and expose it to ultraviolet light (365 nm, 15 W) for 5 minutes. Immerse in a mixed aqueous solution of 6.5 g HEMA, 0.01 g MBAA, 0.02 g (NH4)2S2O8 and 0.0034 g 3APBA, take it out after 5 minutes, place it at room temperature for 10 minutes, rinse it 3 times to remove unreacted monomers, and then place it at room temperature for another 24 hours. A uniform hydrogel coating is formed on the surface of the titanium sheet, which is recorded as Ti-Poly(HEMA-co-3APBA);

[0042] (5) The titanium sheet treated in step (4) was first immersed in a 0.5 mg / mL luteolin ethanol solution for 24 h and then rinsed with ethanol. It was then immersed in a 1.5 mg / mL sophoridine aqueous solution for equilibrium swelling for 24 h. Luteolin was bound through reversible phenylborate, and sophoridine was physically loaded inside the hydrogel. Thus, a titanium implant surface coating that promotes bone integration was prepared, which was recorded as Ti-Poly(HEMA-co-3APBA) / LUT / SOP.

[0043] Example 2

[0044] (1) Take a circular titanium sheet with a diameter of 14.8 mm and a thickness of 1 mm, polish it with #800 and #1600 sandpaper respectively, rinse it with deionized water three times, ultrasonically wash it with acetone, ethanol, and deionized water three times, each time for 5 min, and place it in a 60°C oven to dry;

[0045] (2) The titanium sheet treated in step (1) was immersed in concentrated sulfuric acid and piranha wash solution (98% concentrated sulfuric acid: 30% hydrogen peroxide = 1:1, v / v) in turn, left to stand at room temperature for 1 hour, then taken out, washed with ultrapure water and ethanol three times each, dried, and set aside to introduce hydroxyl groups onto the surface of the titanium sheet, recorded as Ti-OH;

[0046] (3) placing the titanium sheet treated in step (2) in a dopamine hydrochloride solution, wherein the dopamine hydrochloride is dissolved in 10 mM Tris-HCl buffer at a pH of 8.5 to a concentration of 2 mg / mL, soaking overnight in a dark and aerobic conditions, rinsing three times with deionized water, and drying to form a uniform polydopamine coating on the surface of the titanium sheet, which is recorded as Ti-PDA;

[0047] (4) Dissolve 1.182 g of citric acid and 1.018 g of ferric chloride hexahydrate in 30 mL of deionized water, and drop 1 mol / L NaOH solution until the pH reaches 4.0. Then, soak the titanium sheet treated in step (3) in the above solution for 3 hours, and expose the catechol structure of polydopamine to ultraviolet light (365 nm, 15 W) for 5 minutes. Immerse in a mixed aqueous solution of 6.5 g HEMA, 0.01 g MBAA, 0.02 g (NH4)2S2O8 and 0.0034 g 3APBA, take out after 5 minutes, place at room temperature for 10 minutes, rinse 3 times to remove unreacted monomers, and then place at room temperature for 24 hours. A uniform hydrogel coating is formed on the surface of the titanium sheet, which is recorded as Ti-Poly(HEMA-co-3APBA);

[0048] (5) Soak the titanium sheet treated in step (4) in a 0.5 mg / mL luteolin ethanol solution for 24 hours and then rinse with ethanol. A titanium surface hydrogel coating loaded with luteolin alone is prepared, which is recorded as Ti-Poly(HEMA-co-3APBA) / LUT.

[0049] Example 3

[0050] (1) Take a circular titanium sheet with a diameter of 14.8 mm and a thickness of 1 mm, polish it with #800 and #1600 sandpaper respectively, rinse it with deionized water three times, ultrasonically wash it with acetone, ethanol, and deionized water three times, each time for 5 min, and place it in a 60°C oven to dry;

[0051] (2) The titanium sheet treated in step (1) was immersed in concentrated sulfuric acid and piranha wash solution (98% concentrated sulfuric acid: 30% hydrogen peroxide = 1:1, v / v) in turn, left to stand at room temperature for 1 hour, then taken out, washed with ultrapure water and ethanol three times each, dried, and set aside to introduce hydroxyl groups onto the surface of the titanium sheet, recorded as Ti-OH;

[0052] (3) placing the titanium sheet treated in step (2) in a dopamine hydrochloride solution, wherein the dopamine hydrochloride is dissolved in 10 mM Tris-HCl buffer at a pH of 8.5 to a concentration of 2 mg / mL, soaking overnight in a dark and aerobic conditions, rinsing three times with deionized water, and drying to form a uniform polydopamine coating on the surface of the titanium sheet, which is recorded as Ti-PDA;

[0053] (4) Dissolve 1.182 g of citric acid and 1.018 g of ferric chloride hexahydrate in 30 mL of deionized water, and drop 1 mol / L NaOH solution until the pH reaches 4.0. Then, soak the titanium sheet treated in step (3) in the above solution for 3 hours, and expose the catechol structure of polydopamine to ultraviolet light (365 nm, 15 W) for 5 minutes. Immerse in a mixed aqueous solution of 6.5 g HEMA, 0.01 g MBAA, 0.02 g (NH4)2S2O8 and 0.0034 g 3APBA, take out after 5 minutes, place at room temperature for 10 minutes, rinse 3 times to remove unreacted monomers, and then place at room temperature for 24 hours. A uniform hydrogel coating is formed on the surface of the titanium sheet, which is recorded as Ti-Poly(HEMA-co-3APBA);

[0054] (5) The titanium sheet treated in step (4) was immersed in a 1.5 mg / mL aqueous solution of sophoridine for 24 h and then rinsed with water to prepare a titanium surface hydrogel coating loaded with sophoridine alone, which was recorded as Ti-Poly(HEMA-co-3APBA) / SOP.

[0055] Example 4

[0056] (1) Take a circular titanium sheet with a diameter of 14.8 mm and a thickness of 1 mm, polish it with #800 and #1600 sandpaper respectively, rinse it with deionized water three times, ultrasonically wash it with acetone, ethanol, and deionized water three times, each time for 5 min, and place it in a 60°C oven to dry;

[0057] (2) The titanium sheet treated in step (1) was immersed in concentrated sulfuric acid and piranha wash solution (98% concentrated sulfuric acid: 30% hydrogen peroxide = 1:1, v / v) in turn, left to stand at room temperature for 1 hour, then taken out, washed with ultrapure water and ethanol three times each, dried, and set aside to introduce hydroxyl groups onto the surface of the titanium sheet, recorded as Ti-OH;

[0058] (3) The titanium sheet treated in step (2) was immersed in a mixed aqueous solution of 6.5 g HEMA, 0.01 g MBAA, 0.02 g (NH4)2S2O8 and 0.0034 g 3APBA, taken out after 5 minutes, placed at 65°C for 10 minutes, rinsed 3 times to remove unreacted monomers, and then placed at room temperature for 24 hours. A uniform hydrogel coating was formed on the surface of the titanium sheet.

[0059] (4) The titanium sheet treated in step (3) was first immersed in a 0.5 mg / mL luteolin ethanol solution for 24 h and then rinsed with ethanol. It was then immersed in a 1.5 mg / mL sophoridine aqueous solution for equilibrium swelling for 24 h and rinsed with water to prepare a hydrogel coating of two drugs loaded on a titanium surface without polydopamine.

[0060] Test Example 1

[0061] This test example detects the surface morphology and coating structure of the hydrogel coating on the titanium implant surface that promotes bone integration prepared in Example 1, the interface bonding strength of the hydrogel coating on the titanium implant surface obtained in Examples 1 and 4, and the release behavior of sophoridine and luteolin in Examples 1, 2, and 3.

[0062] Surface morphology detection of hydrogel coating:

[0063] (1) Macroscopic changes of titanium sheets and titanium nails in each group are as follows Figure 2 As shown in the figure, the surface of Ti-OH shows a rougher morphology than the original titanium sheet due to acid etching, and a uniform black coating is formed on the surface of Ti-PDA. This is because the polydopamine coating formed on the surface can be evenly spread over the entire surface. A dense and uniform hydrogel coating can be observed on the surface of sample C, and the coating surface shows a slight yellow color due to the loading of two drugs. In addition, the hydrogel coating can cover titanium screw implants with complex geometries.

[0064] (2) Figure 3 Scanning electron microscopy (SEM) was used to characterize the changes in surface morphology during sample preparation. Low-magnification imaging showed that all samples had smooth surfaces and uniform surface structures. The pure titanium surface was relatively smooth, and the surface treated with piranha lotion showed the morphology of a nanoporous network. The SEM results of the Ti-PDA sample showed that the assembled polydopamine coating was dense and crack-free, covering the entire surface. The hydrogel coating prepared on Ti-Poly(HEMA-co-3APBA) was a thicker and denser organic structure that shielded the underlying topology. In addition, in addition to the dense hydrogel coating observed on the C surface, a small amount of particles could be observed, which may be due to the loading of the drug. For titanium implants with complex geometries, such as titanium nails, the Poly(HEMA-co-3APBA) coating can be uniformly attached to its surface. The above results indicate the successful preparation of the hydrogel coating on the titanium surface and its uniform distribution on the titanium surface.

[0065] (3) The surface roughness of different samples was measured using an atomic force microscope, and the arithmetic average roughness (Ra) was used to reflect the roughness. Figure 4As shown, the average Ra values ​​were 29.466, 22.334, 0.674, and 5.765 nm, respectively. The results showed that after the introduction of the polydopamine layer, the surface roughness of the sample decreased slightly, and there was no significant difference between the Ti-OH group and the Ti-PDA group. The subsequent Poly(HEMA-co-3APBA) coating led to a significant decrease in the surface roughness of the sample, indicating that the hydrogel coating can completely shield the underlying topological structure. After loading the drug, the surface roughness of the sample increased. The results show that the special surface structure of the synthesized material can promote cell adhesion, proliferation, and differentiation.

[0066] Hydrogel coating structure detection:

[0067] (4) Figure 5 The Fourier transform infrared spectrum shows that at 1636 cm −1 (C=O), 1541 cm −1 (NH), 1150 cm −1 (C-N), 1050 cm −1 (CO) and 940 cm −1 There is a significant chemical functional group peak at (Ti-OH). −1 The overlapping absorption bands in the range correspond to the Ti-O bonds (Ti-OH and Ti-O-Ti) generated by the native oxide and the surface hydroxide, while in the Ti-OH spectrum the absorption band at 940 cm −1 There is an obvious Ti-OH absorption peak at 1541 cm-1. This indicates that the surface after alkali treatment contains abundant OH groups. After dopamine hydrochloride treatment, the NH bending vibration absorption peak in the Ti-PDA spectrum is 1541 cm-1. −1 (The characteristic peak of amide II bond is 1620 ~ 1510 cm −1 ), proving that the polydopamine coating was successfully constructed on the titanium surface. After gradually constructing the polydopamine / poly(HEMA-co-3APBA) multilayer film, some new peaks appeared in the spectrum of C: the carbonyl (C=O) stretching vibration absorption peak was 1636 cm −1 ; The stretching vibration absorption peak of CN is 1150 cm −1 (The characteristic peak of amide III bond is 1230 ~ 1030 cm −1 ). 1750 ~ 1700 cm −1 The peak band belongs to the stretching of C=O in COOH of HEMA and 3APBA, 1350 cm −1 The peak band belongs to the bending vibration of α-methyl (α-CH3). In the high wavenumber spectral range, 3,500 to 3,000 cm −1The broad bands were assigned to the fundamental stretching vibrations of different OH groups (free or bounded), indicating the successful construction of the hydrogel coating. Comparing the FTIR spectra before and after drug loading, a new peak appeared at 1390 cm-1 and 880 cm-1, which was caused by the asymmetric and symmetric vibrations of the BO bond of the phenylboronic acid group after the formation of the boronate bond. The above results show the successful preparation of the hydrogel coating and verify the formation of chemical bonds therein.

[0068] Test of the bonding strength between hydrogel coating and titanium interface:

[0069] The bonding strength of the prepared coating was studied using a universal testing machine. The titanium sheet with the hydrogel coating on the surface obtained in Examples 1 and 4 was bonded to two identical steel plates on the surface and the reverse side using an epoxy adhesive (loctite450, USA). The load was applied in the shear tensile test with a crosshead speed of 50 mm / min. The bonding strength was calculated using the following formula:

[0070] (r is the radius of the titanium sheet, and the fracture force F is given directly by the machine)

[0071] The bonding strength and toughness retention of the hydrogel coating were studied by fatigue test. The shear tensile test used 5 consecutive loading and unloading tests with a crosshead speed of 50 mm / min and a displacement of 0.1 mm. The maximum stress was directly obtained from the stress-displacement curve.

[0072] (5) Figure 6 As shown in A, in order to evaluate the adhesion between titanium implants and coatings, a bonding shear strength test was performed. Polydopamine is deposited on the Ti-OH surface and strongly bonded to it, forming a polydopamine anchoring layer, which provides abundant reactive groups. The bonding strength of the dopamine-modified titanium hydrogel coating on the material is much higher than that of pure titanium, with an average bonding strength of 3348.3 kP ( Figure 6 B). The presence of polydopamine coating enhances the adhesion strength between the hydrogel coating and the substrate. Since titanium implants are subjected to repeated mechanical forces during implantation in vivo, it is necessary to study the fatigue resistance of Ti-Poly (HEMA-co-3APBA) / SOP / LUT coating. Figure 6C shows the force-displacement curve of Ti-Poly(HEMA-co-3APBA) / SOP / LUT under five consecutive loading-unloading tests. It can be found that after three consecutive loading-unloading tests, the bonding strength of the Ti-Poly(HEMA-co-3APBA) / SOP / LUT coating dropped to 80% of the initial bonding strength (6D). However, from the fourth time onwards, the bonding strength remained basically unchanged. In summary, the prepared a coating has a high bonding strength. In addition, it also has excellent mechanical stability and fatigue resistance under repeated stress.

[0073] Sophoridine and luteolin release behavior detection:

[0074] (6) Figure 7 As shown in the figure, the sustained release behaviors of Ti-Poly(HEMA-co-3APBA) / SOP / LUT, Ti-Poly(HEMA-co-3APBA) / LUT, and Ti-Poly(HEMA-co-3APBA) / SOP three composite hydrogels in a simulated physiological fluid environment (pH=7.4) were studied. A is a schematic diagram of Ti-Poly(HEMA-co-3APBA) / SOP sustained release of sophoridine, B is a schematic diagram of Ti-Poly(HEMA-co-3APBA) / SOP / LUT sustained release of luteolin and sophoridine, and C is a schematic diagram of Ti-Poly(HEMA-co-3APBA) / LUT sustained release of luteolin. The results showed that the luteolin-loaded group released slowly due to the presence of the phenylboronic acid ester bond, while the sophoridine-loaded group released sophoridine faster through physical diffusion. In the sophoridine-loaded and luteolin-loaded groups, sophoridine was released first and quickly in the first two days, and luteolin was almost not released. After the release of sophoridine, the internal pH of the hydrogel decreased. When it reached below 8.2, the boric acid ester bond broke, and luteolin was subsequently released. Sophoridine and luteolin showed obvious timed release, and the overlapping release time between the two was very short.

[0075] Test Example 2

[0076] This test example tests the biocompatibility of the hydrogel coating on the surface of the titanium implant for promoting bone integration prepared in Examples 1, 2, and 3, and its effect on the polarization state of macrophages.

[0077] (1) CCK-8 assay and live / dead cell staining were used to evaluate the cytotoxicity of different samples to mouse mononuclear macrophage leukemia cells and bone marrow mesenchymal stem cells. The CCK-8 results showed that there was no difference in cell proliferation among different groups ( Figure 8 B, D). Live cell / dead cell results are as follows Figure 8As shown in (A, C). Each group mainly emits green fluorescence and rarely emits red fluorescence, indicating that a large number of living cells and a small number of dead cells were observed. The results show that the modified material has good biocompatibility.

[0078] (2) If Fig. 9 As shown, q-PCR analysis was first used to study the effects of different materials on macrophage polarization by detecting the expression of pro-inflammatory and anti-inflammatory genes in RAW264.7 cells after culturing with different titanium implants for 2 and 4 days. The results showed that on the second day, the expression levels of pro-inflammatory factors TNF-α and IL-1β (M1 markers) in the Ti-Poly(HEMA-co-3APBA) / SOP / LUT group were higher than those in the Ti-Poly(HEMA-co-3APBA) / LUT and Ti groups, and the expression of IL-4 and IL-10 (M2 markers) in the Ti-Poly(HEMA-co-3APBA) / SOP group and the Ti-Poly(HEMA-co-3APBA) / SOP / LUT group was reduced, and the proportion of M1 macrophages was increased. This may be due to the fact that the first release of SOP stimulated M1 polarization. On day 4, especially in the Ti-Poly(HEMA-co-3APBA) / LUT / SOP group, the expression of TGF-β and IL-10 increased due to the subsequent release of LUT, while the expression of TNF-α and IL-1β decreased relatively. In addition, the secretion trend of TNF-α and IL-10 in the supernatant detected by ELISA was consistent with the results of qRT-PCR ( Fig. 9 B).

[0079] (3) If Fig.10As shown in the figure, the expression of iNOS (M1 marker) and CD206 (M2 marker) was detected by cell immunofluorescence staining to study the effect of the samples on RAW264.7 cell polarization and observe whether the samples can regulate macrophage polarization. RAW264.7 cells were co-cultured with different titanium for 2 and 4 days, and the expression of iNOS and CD206 was observed by immunofluorescence staining. On the second day, the expression of iNOS in the Ti-Poly(HEMA-co-3APBA) / LUT / SOP and Ti-Poly(HEMA-co-3APBA) / SOP groups was the highest, indicating that the SOP released by the two materials significantly activated M1 polarization. Compared with the above two groups, the expression of iNOS in the Ti-Poly(HEMA-co-3APBA) / LUT group was significantly reduced, indicating that the LUT released by Ti-Poly(HEMA-co-3APBA) / LUT can inhibit the activation of M1 polarization. On day 4, compared with day 2, the expression of iNOS in the Ti-Poly(HEMA-co-3APBA) / LUT / SOP group decreased, and the expression of CD206 increased, indicating that the proportion of M1 macrophages increased. The expression of iNOS in the Ti-Poly(HEMA-co-3APBA) / SOP group further increased, indicating that the proportion of M2 macrophages increased. The above results indicate that Ti-Poly(HEMA-co-3APBA) / LUT / SOP can induce the polarization of pro-inflammatory M1 macrophages on days 1 to 2, and the polarization of anti-inflammatory M2 macrophages on days 3 to 5.

[0080] (4) In addition to having an immunomodulatory effect, an ideal bone implant should also have good osteogenic activity. In order to study whether the factors secreted by RAW264.7 cells stimulated by different titanium implants would affect the osteogenic differentiation of bone marrow mesenchymal stem cells, the present invention used RAW264.7 cell conditioned medium (CM) cultured with different titanium implants for 4 days to culture bone marrow mesenchymal stem cells. On the 14th day, the activity of ALP was determined by staining with a BCIP / NBT alkaline phosphatase colorimetric kit. The ALP staining results showed that the Ti-Poly(HEMA-co-3APBA) / LUT / SOP group had the highest ALP expression and calcium deposition ( Fig.11 A, B). In addition, the ARS staining method is to fix the cells and then stain them with alizarin red dye. Different CMs were incubated for 21 days, and calcium deposition was measured using ARS staining. Consistent with the ALP activity, the amount of mineral deposition in the Ti-Poly(HEMA-co-3APBA) / LUT / SOP group was slightly higher than that in the Ti-poly(HEMA-co-3APBA) / LUT group, but significantly higher than that in the Ti group and the Ti-Poly(HEMA-co-3APBA) / SOP group. The above results indicate that Ti-Poly(HEMA-co-3APBA) / LUT / SOP-mediated immune regulation can significantly promote the osteogenic differentiation of bone marrow mesenchymal stem cells.

[0081] Test Example 3

[0082] This test example tests the in vivo angiogenesis and bone integration performance of the hydrogel coating on the surface of the titanium implant prepared in Examples 1, 2, and 3.

[0083] (1) To evaluate the vascularization around the implants, H&E and immunohistochemical staining were performed on the samples on day 7, and CD31 was selected as a typical vascular marker. The CD31 positive level was the lowest in the Ti group, while the Ti-Poly(HEMA-co-3APBA) / SOP / LUT group showed obvious CD31 positive blood vessels with the largest number ( Fig.12 ). At the same time, in the H&E staining results, obvious vascular structures were observed in both Ti-Poly(HEMAco-3APBA) / SOP / LUT and Ti-Poly(HEMA-co-3APBA) / LUT groups. However, slightly different from the results of macrophage-driven in vitro angiogenesis, the vascular network in the Ti-Poly(HEMA-co-3APBA) / SOP / LUT group was more mature and the vessel diameter was larger. The Ti-Poly(HEMA-co-3APBA) / SOP / LUT group had the most CD31-positive vessels and the most mature vascular network.

[0084] (2) Micro-CT analysis and 3D reconstruction showed that the Ti-Poly(HEMA-co-3APBA) / LUT / SOP group had more new bone formation and a more complete structure than the other groups ( Fig.13 A). The study calculated the percentage of new bone volume to total bone volume (BV / TV), the number of trabeculae (Tb.N) and the trabecular spacing (Tb.Sp), such as Fig.13 As shown in B, the trabecular spacing showed an opposite trend, which was consistent with the Micro-CT results. These results all confirmed that the Ti-Poly (HEMA-co-3APBA) / LUT / SOP group had the best osteogenic ability.

[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a titanium implant surface coating that promotes bone integration, characterized in that: The following steps are involved: (1) The original titanium sheet was polished with sandpaper, washed with different solvents, and dried; (2) Soaking the titanium sheet treated in step (1) in concentrated sulfuric acid and piranha wash solution in turn, leaving it at room temperature for a period of time, then taking it out, washing it with ultrapure water and ethanol three times each, drying it, and setting it aside; (3) soaking the titanium sheet treated in step (2) in a dopamine hydrochloride solution overnight in a dark and aerobic environment, rinsing with water, and drying; (4) The titanium sheet treated in step (3) is immersed in a mixed solution of ferric chloride hexahydrate and citric acid, taken out and exposed to ultraviolet light, and then immersed in a mixed solution of hydroxyethyl methacrylate monomer, taken out and left at room temperature overnight; the monomer solution of hydroxyethyl methacrylate is hydroxyethyl methacrylate, N , A mixed solution formed by N-methylenebisacrylamide, ammonium persulfate and 3-acrylamidophenylboric acid; (5) The titanium sheet treated in step (4) is sequentially immersed in an alcohol solution of luteolin and a sophoridine solution for equilibrium swelling, thereby preparing a titanium implant surface coating that promotes bone integration.

2. The method for preparing a titanium implant surface coating that promotes bone integration according to claim 1, characterized in that: The solvent in step (1) includes acetone, ethanol, and deionized water for ultrasonic washing; In step (2), the concentration of concentrated sulfuric acid is 98% or above; the piranha wash solution is 98% or above concentrated sulfuric acid and 30-40% hydrogen peroxide in a volume ratio of 3-5:

1.

3. The method for preparing a titanium implant surface coating that promotes bone integration according to claim 1, characterized in that: The dopamine hydrochloride in step (3) is dissolved in 5-10 mM Tris-HCl buffer, pH 8.0-8.5, with a concentration of 2-5 mg / mL.

4. The method for preparing a titanium implant surface coating that promotes bone integration according to claim 1, characterized in that: The specific steps in step (4) are: In the mixed solution, the mass concentration of ferric chloride hexahydrate is 0.03-0.04 g / mL; the mass concentration of citric acid is 0.03-0.04 g / mL; and the pH value of the mixed solution is adjusted to 3-5 before soaking.

5. The method for preparing a titanium implant surface coating that promotes bone integration according to claim 1, characterized in that: The ultraviolet light conditions are 300-370 nm and 10-20 W for 3-10 minutes.

6. The method for preparing a titanium implant surface coating that promotes bone integration according to claim 1, characterized in that: In the monomer solution of hydroxyethyl methacrylate, hydroxyethyl methacrylate, N , The concentrations of N-methylenebisacrylamide, ammonium persulfate and 3-acrylamidophenylboronic acid were 1-1.5 g / mL, 1-3 mg / mL, 2-5 mg / mL and 0.5-0.7 mg / mL, respectively.

7. The method for preparing a titanium implant surface coating that promotes bone integration according to claim 1, characterized in that: In the step (5), the concentration of the alcohol solution of luteolin is 0.1-1.0 mg / mL, and the alcohol solution comprises a C1-C4 alcohol solvent; The concentration of the sophoridine is 1.0-5.0 mg / mL.

8. The method for preparing a titanium implant surface coating that promotes bone integration according to claim 7, characterized in that: In the step (5), the concentration of the alcohol solution of luteolin is 0.5 mg / mL; the concentration of sophoridine is 1.5 mg / mL.

9. A titanium implant surface coating for promoting bone integration prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the titanium implant surface coating promoting bone integration prepared by the preparation method according to any one of claims 1 to 8 in the preparation of a drug for treating implant bone integration.

11. Use of the titanium implant surface coating promoting bone integration prepared by the preparation method according to any one of claims 1 to 8 in the preparation of a drug for preventing insufficient bone integration of implants.

Citation Information

Patent Citations

  • Bone induction and immunization double-effect coating, preparation method and application in osseointegration

    CN113368305A

  • Polymer micelle coating for sequentially delivering immunomodulatory factors on surface of nanorod array and preparation method and application thereof

    CN114010837A